Tinjauan Yuridis Kewenangan DKPP Menurut Undang-Undang Nomor 15 Tahun 2011 Terhadap Putusan DKPP Nomor : 23 -25/DKPP-PKE-I/2012 - William Hendri (Jurnal Selat, 2014)
The Honorable General Elections Administrator Council (DKPP) was formed to check and decide on the complaints and/or reports about ethical codes violation allegations done by General Elections Administrator based on the mandate of Undang-undang Number 15 Year 2011 about General Elections Administrator. However, in reality, DKPP issuing a verdict was controversial because it was not its authority. The problems and the objectivesof this research were: 1) Determining how the authority of DKPP in handling the problems in general elections, and 2) Evaluating DKPP verdict Number 23 -25/DKPP-PKE-I/2012 pursuant to Undang-Undang Number 15 Year 2011 about General Elections Administrator. The method used was normative law research method using secondary data. The secondary data gathered from the library research was arranged in order and systematically to be analyzed using qualitative method to get the picture about the main problem comprehensively. This research showed that DKPP was a council formed to guard the ethics in the general elections. DKPP was an ethical institution assigned by Undang-undang Number 15 Year 2011. The authority of DKPP related to General Elections Administrator ethical codes enforcement was attributive and based on clause 109 verse (2), clause 111 verse (1), and also clause 112 verse (10) and (11). In fact, with the verdict of DKPP Number 23 -25/DKPP-PKE-I/2012, about legislative members general elections arrangement proses in 2014, DKPP verdict was considered controversial by telling KPU to do the factual verification on 18 political parties which were avowed did not fulfill the administration verification by KPU. It meant that DKPP made a decision which contradicted clause 1 verse 3 UUD 1945 which was in line with legality principle. About the DKPP verdict to be final and bounding was mentioned on clause 112 verse (12) where the defendants and the related parties could not do any legal efforts as experienced by the board of KPU secretary generals. This was quite contrary with UUD 1945 clause 28D verse (1) about legal protection rights and legal certainty which is as equal as possible in front of the law if the verdict issued was felt harming the defendants or the related parties. Keywords: Review, Juridical, Council, Honorable, General Elections.